2013
DOI: 10.1039/c3cp50638j
|View full text |Cite
|
Sign up to set email alerts
|

Mg-doped VO2 nanoparticles: hydrothermal synthesis, enhanced visible transmittance and decreased metal–insulator transition temperature

Abstract: This paper reports the successful preparation of Mg-doped VO2 nanoparticles via hydrothermal synthesis. The metal-insulator transition temperature (T(c)) decreased by approximately 2 K per at% Mg. The Tc decreased to 54 °C with 7.0 at% dopant. The composite foils made from Mg-doped VO2 particles displayed excellent visible transmittance (up to 54.2%) and solar modulation ability (up to 10.6%). In addition, the absorption edge blue-shifted from 490 nm to 440 nm at a Mg content of 3.8 at%, representing a widened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
156
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 36 publications
16
156
0
3
Order By: Relevance
“…7 Doping is a well-established way to decrease τ c , 23 with tungsten as the superior dopant capable of reducing τ c by as much as ~25 °C/at.% W for well-crystallized films, made by a variety of techniques, 7 without severely deteriorating the optical performance. 24 Magnesium doping was found to be able to increase T lum and to simultaneously decrease τ c by ~3 °C/at.% Mg; 1,25 the boost in optical performance was seen to be connected with band gap widening and concomitant lowering of the spectral absorptance in the luminous wavelength range. 8,10 These features could be reconciled with hybrid functional calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Doping is a well-established way to decrease τ c , 23 with tungsten as the superior dopant capable of reducing τ c by as much as ~25 °C/at.% W for well-crystallized films, made by a variety of techniques, 7 without severely deteriorating the optical performance. 24 Magnesium doping was found to be able to increase T lum and to simultaneously decrease τ c by ~3 °C/at.% Mg; 1,25 the boost in optical performance was seen to be connected with band gap widening and concomitant lowering of the spectral absorptance in the luminous wavelength range. 8,10 These features could be reconciled with hybrid functional calculations.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Recent modeling studies on "nanothermochromics" 4,5 have shown that VO 2 nanoparticles can offer significantly higher values of T lum and ΔT sol than films, and these new possibilities have led to a burst of research on such nanoparticles. 6,9,19,22,25,[30][31][32][33][34] 25 This paper is outlined as follows: Section II reports on the samples and treats sputter deposition, compositional and structural data, and optical characterization and properties; this section also contains a discussion of sample quality which-as found in recent work of ours 9 -may be critically dependent on several aspects of the thin film preparation. Section III contains results and discussions for undoped and Mg-doped VO 2 thin films without and with AR coatings as well as for nanoparticle composites containing the same VO 2 -based materials.…”
Section: Introductionmentioning
confidence: 99%
“…TC fenestration has been discussed for several decades [2][3][4][5][6][7][8][9][10], but practical implementation has been hampered by performance deficiencies such as a too high value of τ c , too large luminous absorptance, and too small modulation of the solar energy throughput [11]. However, there has been substantial progress towards the alleviation of all of these obstacles, and it is well known that tungsten doping can decrease τ c to room temperature [11,12], that luminous absorptance can be lowered by magnesium doping [13][14][15][16], and that solar energy modulation can be boosted by invoking VO 2 -based nanoparticles rather than thin films [16][17][18]. Another obvious requirement for practical implementation of TC VO 2 -based films and nanoparticles is that they must maintain their desirable properties during extended periods of time, which is far from obvious since V 2 O 5 , not VO 2 , is the thermodynamically stable oxide [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming indirect-allowed transitions, two bandgaps can be extracted: at $0.5 eV and at a value exceeding $1.6 eV. 21,22 The larger bandgap is most relevant for the luminous transmittance and was investigated in this work; it has been assigned to transitions from predominantly O2p to V3d t 2g states. 13,21 Figure 3 shows examples of bandgap evaluations employing optical constants obtained from the "surface þ back" method for samples with z ¼ 0 and 0.088; the corresponding values of E g were 1.71 and 2.04 eV, respectively.…”
mentioning
confidence: 99%
“…18,19 Doping with Mg is another approach to boost the luminous transmittance of VO 2 as experimentally discovered 20 and subsequently theoretically corroborated through hybrid-functional computations; 21 this doping also lowers s c . 20 Nanothermochromics with Mg-doped VO 2 was realized recently 22 and demonstrated improved luminous transmittance and additional benefits, of interest for practical fenestration, such as a less yellowish appearance. We are not aware of any prior, quantitative study on the effect of Mg-doping on the bandgap of VO 2 , even though such information is essential for the design of Mg-doped VO 2 -based materials.…”
mentioning
confidence: 99%